Dragon ghosts - McMann, Lisa (McMann, Lisa. Unwanteds quests, 2019)
The civil war rages in the Land of the Dragons, and Fifer and Simber struggle to keep their team together in the search for Fifer's twin. Meanwhile, Thisbe considers abandoning Rohan in a gamble that could bring her home or kill her. In Artimé a mage step up to bring peace but discovers that the Revinir's power has reached the capital.